JALAN BERLIKU MENUJU PENETAPAN ANGGARAN PENDAPATAN DAN BELANJA DAERAH TEPAT WAKTU (Study Proses Penyusunan dan Penetapan APBD Kabupaten Blitar) - Department, administratio; Laksono, Fia (Administratio, 2017)
ABSTRACT. This paper examines managerial and political dimensions of local budgetpreparation and approval process. Data derived from observation, interviews anddocumentation. Results of the analysis showed that in the process of preparation andadoption of Blitar Regency’s Local Budget of Fiscal Year 2013-2015, the managerialdimension occurs in stages preparation and adoption RKPD, KUA PPAS preparation,preparation of the budget document and budget evaluation process, while the politicaldimension occurs in discussion phase and the memorandum of understanding KUA PPAS,discussion and approval of the budget and the budget determintaion. As a series of cyclesof preparation and approval of the budget process when a late stage would affect thewhole stage. Changes in regional governance law of Act 32 of 2004 into Act 23 of 2014which set of sanctions against the head region and Parliament when the budget late set apositive influence on the timeliness of APBD. In conclusion, the sanctions regents andDPRD positive effect on the timeliness of the determination of Blitar Regency’s LocalBudget of Fiscal Year 2015 differs with the approval of Blitar Regency’s Local Budget inthe previous year always late set. Keywords: APBD, budget preparation dan approval process, late budget, sanction,Kabupaten Blitar